Laser‐facilitated epicutaneous immunotherapy with hypoallergenic beta‐glucan neoglycoconjugates suppresses lung inflammation and avoids local side effects in a mouse model of allergic asthma. Issue 1 (16th July 2020) - Korotchenko, Evgeniia; Schießl, Viktoria; Scheiblhofer, Sandra; Schubert, Mario; Dall, Elfriede; Joubert, Isabella A.; Strandt, Helen; Neuper, Theresa; Sarajlic, Muamera; Bauer, Renate; Geppert, Mark; Joedicke, David; et al.
Abstract: Background: Allergen‐specific immunotherapy via the skin targets a tissue rich in antigen‐presenting cells, but can be associated with local and systemic side effects. Allergen‐polysaccharide neoglycogonjugates increase immunization efficacy by targeting and activating dendritic cells via C‐type lectin receptors and reduce side effects. Objective: We investigated the immunogenicity, allergenicity, and therapeutic efficacy of laminarin‐ovalbumin neoglycoconjugates (LamOVA). Methods: The biological activity of LamOVA was characterized in vitro using bone marrow‐derived dendritic cells. Immunogenicity and therapeutic efficacy were analyzed in BALB/c mice. Epicutaneous immunotherapy (EPIT) was performed using fractional infrared laser ablation to generate micropores in the skin, and the effects of LamOVA on blocking IgG, IgE, cellular composition of BAL, lung, and spleen, lung function, and T‐cell polarization were assessed. Results: Conjugation of laminarin to ovalbumin reduced its IgE binding capacity fivefold and increased its immunogenicity threefold in terms of IgG generation. EPIT with LamOVA induced significantly higher IgG levels than OVA, matching the levels induced by s.c. injection of OVA/alum (SCIT). EPIT was equally effective as SCIT in terms of blocking IgG induction and suppression of lung inflammation and airway hyperresponsiveness, but SCIT was associated with higher levels of therapy‐induced IgE and TH2 cytokines. EPIT with LamOVA induced significantly lower local skin reactions during therapy compared to unconjugated OVA. Conclusion: Conjugation of ovalbumin to laminarin increased its immunogenicity while at the same time reducing local side effects. LamOVA EPIT via laser‐generated micropores is safe and equally effective compared to SCIT with alum, without the need for adjuvant. Abstract : Epicutaneous immunotherapy (EPIT) targets a tissue rich in antigen‐presenting cells. Laser‐facilitated EPIT combines controlled and efficient barrier disruption with a laser‐induced adjuvant effect. However, application of native allergens to the skin can induce unwanted side effects. Coupling the β‐glucan laminarin to allergens can markedly reduce their IgE binding capacity. β‐glucan neoglycoconjugates efficiently target dendritic cells via the C‐type lectin receptor dectin‐1, boosting their immunogenicity. In a mouse model of allergic asthma, laminarin‐ovalbumin conjugates (LamOVA) diminished local side effects in vivo, while inducing higher levels of blocking IgG compared with uncoupled OVA. EPIT with LamOVA was equally efficient in improving lung functions compared to classical SCIT. Abbreviations: EPIT, epicutaneous immunotherapy; LamOVA, laminarin‐ovalbumin conjugates; OVA, ovalbumin; PBS, phosphate‐buffered saline; Penh, resistance and compliance data are shown as area under the curve (AUC) of a methacholine challenge dose response curve; SCIT, subcutaneous immunotherapy